(untitled) (International Journal of Engineering and Computer Science, 2017)
Let us think of education as the means of developing our greatest abilities, because in each of us there is a private hope and dream which, fulfilled, can be translated into benefit for everyone and greater strength for our nation. –John F. Kennedy. John F. Kennedy‘s quote about the goal of education could very well be applied to the social and economic progress of a country. Crowd funding has emerged in education as a means to make private dreams a reality through collective micro financing. The flip side of the story is that, while a segment of the population receives quality education, most underprivileged kids are deprived of this basic need. College tuition costs have rocketed up over the past decade and experts expect education costs to continue their upward trajectory over the coming years. Crowd funding is the practice of funding a project or venture by raising funds from a large number of people, often performed via internet-mediated registries. The cycle is viscous—you educate one generations follow. By ensuring quality education, one is assured of their right for a better life. In the face of increased competition and diminishing federal funding, some academicians and students are turning to crowd funding platforms to raise money. This paper is intended to study the challenges facing crowd funding and understanding the level of awareness about this emerging source of finance among the masses for the advancement of education.